A COMPARISON OF TIME-VARYING VOLATILITY OF ISLAMIC AND CONVENTIONAL STOCK MARKETS IN INDONESIA - Sukma, Arie (Buletin Studi Ekonomi, 2023)
Using daily data from January 2003 to December 2021, this paper examines the impact of structural changes on the volatility of Islamic and conventional stocks in Indonesia. Assuming that there are two regimes (regular and turbulence) due to these structural changes and using the MS-GARCH model, this paper finds that the volatility of Islamic and conventional stocks in Indonesia has a different pattern based on the regime. The volatility of Islamic and conventional stocks tends to increase during turbulence compared to regular periods. However, the negative effect of domestic shocks is more significant on stock volatility than on foreign shocks. In addition, this study also found that the response of Islamic and Conventional stocks looks different. This finding implies differences in characteristics between Islamic and conventional stocks responding to structural shocks.